MODELING RATING OF SCIENTIFIC AND TECHNOLOGICAL DEVELOPMENT OF THE COUNTRIES - Olena Reshetnyak (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the article is rating assessment and development of recommendations on management of scientific and technological development of the countries. The purpose of the article is to develop an index that assesses the scientific and technological potential, the results of scientific and technological activities and the pace of changes in the scientific and technological development of different countries of the world. The following tasks are solved in the article: the model of rating estimation of scientific and technical development of the countries of the world is developed; the countries of the world are classified depending on a level of their scientific and technical development; recommendations on development of scientific and technical potential of the countries depending on the chosen groups are given. The following methods are used: indexing method, ranking and grouping. The following results were obtained: the calculations possible to identify three groups of countries according to the level of their scientific and technological development: leaders, potential leaders and "overtaking" countries. Main result of the project is to promote the development of the scientific and technological potential, to demonstrate the insignificant results of the scientific and technological activity, and to reduce the low level of development of new technologies. For each of the above groups of countries, recommendations have been made for raising the level of their scientific and technological development. Conclusions: the current stage of the world’s technological development creates new opportunities for the countries of the world to ensure their sustainable growth. Therefore, the creating and maintaining the potential of scientific and technological development, coupled with an adequate government policy of economic development, opens up tremendous opportunities for the countries to ensure global competitiveness. The study presented provides general recommendations for individual countries to improve the processes of managing scientific and technological potential of individual groups of countries. The obtained results can become the basis for the concept and strategy development of scientific and technological development of different countries of the world.